Changes in Gender Representation in Academic Grand Rounds Speakers During the COVID-19 Pandemic - Abigail Dereje; Rahel Ghebre; Shanaz Sultan; Ben Langworthy; Michelle N. Rheault (Women's Health Reports)
Introduction: Women are historically underrepresented as grand rounds speakers in US medical schools regardless of department. We hypothesized that the representation of women as grand rounds speakers would increase after the widespread adoption of virtual grand rounds during the COVID-19 pandemic. Methods: We reviewed publicly available or individually provided grand round speaker lists for 2019, 2021, and 2022 from representative medical departments, surgical departments, and basic science departments of our local institution and the top 10 academic medical schools based on their national ranking according to the 2022 Blue Ridge Institute for Medical Research Rankings of NIH Funding. Speaker gender was determined based on name and publicly available biographies. Results: In total, we identified 1995 speaking engagements from 10 institutions. All but six talks delivered post-COVID-19 pandemic were in hybrid or virtual-only format compared to exclusively in-person sessions pre-COVID-19 pandemic. Before the COVID-19 pandemic, women accounted for 37.3% of invited speakers compared to 45.5% post-COVID. This increase in the representation of women as grand rounds speakers was consistent across all academic ranks and most departments. Conclusions: We propose that departments, particularly those with fewer women at baseline, should continue to offer at least some virtual grand rounds opportunities throughout the year with a goal of increasing the diversity of speakers and improving the access of their faculty to women speakers.